CrossTalk opposing view: Diffusion limitation of O2 from microvessels into muscle does not contribute to the limitation of VO2 max - Lundby, C.; Montero, D. (The Journal of Physiology, 2015)
Oxygen is transferred from air to mitochondria in sequential steps by means of diffusion and convection. The theoretical ceiling for whole body aerobic uptake may be determined by any factor influencing the O2 transport and utilization chain. The dispute considered here is whether peripheral O2 diffusion from microvessels, particularly capillaries, into active skeletal muscle fibres limits/regulates maximal oxygen uptake (VO2max) in healthy humans.